Glyphosate biodegradation by plant growth promoting bacteria and their effect to paddy germination in glyphosate contaminated soil - Lutfi Tri Andriani; Luqman Qurrata Aini; Tutung Hadiastono (Journal of Degraded and Mining Lands Management, 2017)
Glyphosate is the most widely used herbicide in Indonesia. Glyphosate persistence between 55 days to 3 years. Widespread and uncontrolled use can cause weeds to become resistant and residue contaminates the soil and water environment. Due to the residual impact of glyphosate, it is necessary to identify a method that can increase the degradation of glyphosate. Several studies have shown that glyphosate can be degraded by microorganisms (fungi, rhizosphere and endophytic bacteria), some of which are members of plant growth-promoting bacteria. This study used the bacteria Enterobacter cloacae, Enterobacter sp and Pseudomonas fluorescens. These three types of bacteria have growth-promoting properties and potentially increase glyphosate degradation. Results of chromatogram on the residual test of glyphosate in liquid medium and soil containing glyphosate showed that glyphosate residue decreased with the addition of bacterial treatment when compared to control. The percentage of degradation in liquid medium are 96.06%  by Enterobacter cloacae, 57% by Enterobacter spand 93.45%  by Pseudomonas fluorescens.The percentage of degradation in soil medium are 4.32%  by Enterobacter cloacae, 23.49% by Enterobacter spand 12.19% by Pseudomonas fluorescens.A positive result indicates that bacterial growth boosters from the plant (endophyte) as well as the area of rooting (rhizosphere) have additional potential as biofertilizer, bio stimulant, bio protectant but also as bio degradator pollutants such as the herbicide glyphosate